2013
DOI: 10.1242/dev.085431
|View full text |Cite
|
Sign up to set email alerts
|

Functional evaluation of ES cell-derived endodermal populations reveals differences between Nodal and Activin A-guided differentiation

Abstract: SUMMARYEmbryonic stem (ES) cells hold great promise with respect to their potential to be differentiated into desired cell types. Of interest are organs derived from the definitive endoderm, such as the pancreas and liver, and animal studies have revealed an essential role for Nodal in development of the definitive endoderm. Activin A is a related TGF member that acts through many of the same downstream signaling effectors as Nodal and is thought to mimic Nodal activity. Detailed characterization of ES cell-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 71 publications
1
57
0
Order By: Relevance
“…However, the inductive pathways leading up to the PDX1 expression are disparate and may result in slightly different outcomes. This is similar to the induction of DE in vitro by activin A versus nodal [100]. Indeed, during early development, the ventral pancreas exhibits a predominance of PP cells and peptide YY-positive cells over other endocrine cell types [38].…”
Section: Generation Of Primitive Gut and Posterior Foregut Tissuesupporting
confidence: 66%
See 2 more Smart Citations
“…However, the inductive pathways leading up to the PDX1 expression are disparate and may result in slightly different outcomes. This is similar to the induction of DE in vitro by activin A versus nodal [100]. Indeed, during early development, the ventral pancreas exhibits a predominance of PP cells and peptide YY-positive cells over other endocrine cell types [38].…”
Section: Generation Of Primitive Gut and Posterior Foregut Tissuesupporting
confidence: 66%
“…This suggests that the choice for either activin A or nodal is perhaps not without consequences for the successful induction of DE and the development of beta-cells downstream of that. Indeed, a recent report demonstrates that the use of nodal instead of activin A results in a greater frequency of mouse ES cell-derived beta-cells, despite only modest initial differences in global gene expression at the DE stage [100].…”
Section: Generation Of Definitive Endodermmentioning
confidence: 99%
See 1 more Smart Citation
“…These protocols vary in parameters such as the formulation of the basic culture medium, the combination of supplements used and the dosage and timing at which they are delivered to the differentiating cells. Of particular interest is that Activin A and Nodal, two TGF-b superfamily factors, have been reported to elicit similar signalling responses and can induce differentiation of embryonic stem cells to DE-like cells with very similar molecular phenotypes [30,34], but Nodal-treated cells display greater functional capacity than their Activin A counterpart to differentiate into functionally competent pancreatic endoderm cells [30]. In our study, we observed different responses of EpiSCs to Nodal and Activin A during differentiation in culture.…”
Section: Nodal Promotes Differentiation Of Epiblast Stem Cells With Ementioning
confidence: 51%
“…Despite the central role of Nodal in specifying endoderm during development, current protocols for directed in vitro differentiation of endoderm derivatives rely on the related ligand Activin A as a surrogate, presumably because Activin is more active than commercially available recombinant Nodal (2)(3)(4)(5)(6)(7)(8). However, a recent study showed that Nodal induces endoderm progenitors that are more competent to mature into functional insulin-producing cells if it is added to cultured mouse ES cells at a 20-fold higher concentration than Activin A (9). As this concentration likely exceeds physiological levels, it is important to determine how the specific activity of recombinant Nodal might be improved.…”
mentioning
confidence: 99%